ANALISIS IKLAN SECARA ON LINE MELALUI MEDIA GADGET TERHADAP MINAT PELAKU KONSUMEN - Lubis, Reniwati; Frianto, Herri Trisna (Yayasan Education and Social Center, 2024)
Nowadays, technology is developing more and more rapidly. With this technology, everything is very easy to do. There is almost no one who doesn't have a Gadet. Gadets are no longer a luxury item but have become a necessity. There are many types of gadgets, from expensive ones to cheap ones that are affordable for the public. Gadget features vary from those with a few features to those with a large number and sophistication. So that MSMEs or entrepreneurs or business people can carry out promotions easily. With Gadgets, promotions can be done directly (on line). The purpose of this research is to find out how interested consumers are in seeing online advertising promotions. The results of this research show that consumer interest in Gadget advertising is high